Distribution of Nitrogen Fractions in Jodhpur Soils - Aggarwal, R K; Dhir, R P; Bhola, S N; Kaul, Pramila (Annals of Arid Zone, 2016)
The soil nitrogen was fractionated into mineralized N, acid hydrolyzable fractions: hydrolyzable NH4-N, aminoacid N, hexosamine N, unidentified N. and acid non-hydrolyzable N forms in six typical soil profiles of Jodhpur district. Non bydrolyzable-N and hydrolyzable-N ranged from 2.5 to 68.8 and 3.2 to 97.5 percent of total N, respectively The relative distribution of different hydrolyzable N fractions was aminoacid N > unidentified-N> ammonium N > hexosamine-N. their contents ranged from 18.8 to 40.0, 14.1 to 50.0, 3. I to 9.4 and 0.8 to 3.1 per cent. respectively of total N in surface soils. The soils were found to be rich in amino acid N but low in hexosamine-N and hydrolysed NH4-N. C/N values were ravrow. Based on simple correlation, organic carbon was significantly positively related to hydrolyzable N, unidentified N and mineralized-N. Hydrolyzable NH4-N was found to be significantly ne2atively related with mineralized-N. Clay content did not bear any significant relationship with either of the organic fractions studied.